Intraoperative Consultation in Gynecologic Pathology: A 6-Year Audit at a Tertiary Care Medical Center. Issue 1 (1st January 2009) - Ismiil, Nadia; Ghorab, Zeina; Nofech-Mozes, Sharon; Plotkin, Anna; Covens, Allan; Osborne, Ray; Kupets, Rachel; Khalifa, Mahmoud A.
Abstract : Background: Most of the literature on intraoperative consultation (IOC) in gynecologic pathology focuses on the accuracy of this technique. This study addresses a wide range of quality assurance issues regarding this practice through a comprehensive audit of our experience. Design: The anatomic pathology database was searched between 1999 and 2005 for all gynecologic cases who received IOCs. Seven hundred thirty-one IOCs rendered were identified and analyzed. The accuracy of IOC by gynecologic pathologists was comparable to that of surgical pathologists. Results: Patient care was potentially negatively impacted in 14 IOCs; 2 were conducted by the former and 12 by the latter group. Management of ovarian tumors with borderline features significantly improved when the terminology of "at least borderline" was used. Intraoperative consultation by gross inspection only had a low accuracy of 94.7%. Intraoperative consultation was able to definitively and correctly answer the question of whether an ovarian tumor was primary or metastatic in only 35% of patients. As a result of the IOC, the surgical procedure proceeded as originally intended in 96% of patients, was modified in 2%, and was terminated in 2%. Conclusions: This audit identifies certain procedural and communication strategies that can increase accuracy. It also highlights the situations where IOC could be less reliable. Patient's safety can increase by improving the communication between the surgeons and the consultant pathologist, consulting with gynecologic pathologists in oncology cases whenever feasible, and using the term of "at least borderline" rather than "borderline."